Pluralisme Agama dan Perubahan Sosial dalam Perspektif Islam - Muhammad Yusuf Wibisono (UIN Sunan Gunung Djati Bandung, 2016)
The Religions it basically teach about human values, the science that teaches the values of humanity, namely pluralism, the pluralism is basically a continuation of the moral attitude of tolerance and coexistence. If the tolerance is modest habit of respecting differences on the surface, while coexistence is to accept the existence of other parties, but not curb conflicts. While pluralism is the spirit of mutual protection and equal endorse and develop a sense of brotherhood among people both as individuals and groups. so that there is cooperation in order to build universal human values, and provide the same opportunity to others, especially his civil rights on behalf of the citizens of the nation, as well as citizens of the world. There is also indicated its universality. Islam as a religion that upholds present high values of pluralism, according the Islamic of spririt liberation became an essential part of Islam by giving priority to do good basis for peaceful coexistence and justice or competing in goodness, (fastabiq-û‘l-khayr-ât). in al -Quran (109: 1-6). And to the attitude of pluralism, the need for dialogue, it is meant to discuss in addition to the equation, also the difference in order to find common ground with each other. The dialogue process in a manner that makes sense and still uphold the dignity and honor of each as a form of recognition of pluralism (diversity). According Glock and Stark that are not easy to measure the religiosity of a person or community (Ummah) on any religion, because it is also necessary to pay attention to -things such as: membership, belief in religious doctrine, ethics and morality, views and ways of life.